2014
DOI: 10.1210/jc.2013-3186
|View full text |Cite
|
Sign up to set email alerts
|

Signaling Through FSH Receptors on Human Umbilical Vein Endothelial Cells Promotes Angiogenesis

Abstract: Our studies reveal a novel role for FSHR in female reproductive physiology. Its ability to promote angiogenesis in placental endothelial cells suggests that the FSHR may have an influential role in pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

10
96
4
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(112 citation statements)
references
References 37 publications
10
96
4
2
Order By: Relevance
“…Because FSH-receptors have been identified on non-gonadal cells including bone osteoclasts [54], tumor blood vessels [57], and uterine and placental cells [55, 56, 58, 59], it would be interesting to determine whether different FSH glycoforms bind and signal via FSH receptors in these non-gonadal cells. Most likely, FSH 21/18 and FSH 24 glycoforms may signal through different pathways in these different cell types.…”
Section: Discussionmentioning
confidence: 99%
“…Because FSH-receptors have been identified on non-gonadal cells including bone osteoclasts [54], tumor blood vessels [57], and uterine and placental cells [55, 56, 58, 59], it would be interesting to determine whether different FSH glycoforms bind and signal via FSH receptors in these non-gonadal cells. Most likely, FSH 21/18 and FSH 24 glycoforms may signal through different pathways in these different cell types.…”
Section: Discussionmentioning
confidence: 99%
“…Since clinical studies have found improved ovarian stimulation with mixtures of acidic and less acidic hFSH isoforms (16) it will be important to determine whether mixtures of hypo-glycosylated FSH and fully-glycosylated FSH contribute to enhanced or diminished biological responses. Understanding how FSH glycoforms direct activities in multiple FSH target tissues [ovary, bone (33,34), endothelium (35), uterus and placenta (36,37)] offers a unique opportunity to develop novel approaches for diagnosis and treatments to improve fertility and reduce age associated morbidity.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to tumor vessel cells (primary and metastatic), it was suggested that FSHR might serve as a potential cellular marker of different tumors and provide a novel approach for targeted cancer therapy. Four-years after the report of FSHR expression in tumor vessel cells14, FSHR expression was demonstrated in human umbilical vein endothelial cells (HUVEC)15. HUVECs significantly responded to FSH treatment in a series of functional tests like tube formation, wound healing, cell migration and proliferation, nitric oxide production and cell survival15.…”
mentioning
confidence: 99%
“…Four-years after the report of FSHR expression in tumor vessel cells14, FSHR expression was demonstrated in human umbilical vein endothelial cells (HUVEC)15. HUVECs significantly responded to FSH treatment in a series of functional tests like tube formation, wound healing, cell migration and proliferation, nitric oxide production and cell survival15. This allowed the authors of above study to propose that HUVECs express functional FSHR expression and that the FSH-FSHR activation promotes angiogenesis as effectively as the potent well-characterized angiogenic factor VEGF15.…”
mentioning
confidence: 99%
See 1 more Smart Citation